Engineered therapeutic antibodies with mannose 6-phosphate analogues as a tool to degrade extracellular proteins - Daurat, Morgane; Gauthier, Corentin; El Cheikh, Khaled; Ali, Lamiaa M. A.; Morère, Elodie; Bettache, Nadir; Gary-Bobo, Magali; Morère, Alain; Garcia, Marcel; Maynadier, Marie; Basile, Ilaria (Frontiers in Immunology, 2024)
Inducing the degradation of pathological soluble antigens could be the key to greatly enhancing the efficacy of therapeutic monoclonal antibodies (mAbs), extensively used in the treatment of autoimmune and inflammatory disorders or cancer. Lysosomal targeting has gained increasing interest in recent years due to its pharmaceutical applications far beyond the treatment of lysosomal diseases, as a way to address proteins to the lysosome for eventual degradation. Mannose 6-phosphonate derivatives (M6Pn), called AMFA, are unique glycovectors that can significantly enhance the cellular internalization of the proteins conjugated to AMFA via the cation-independent mannose 6-phosphate receptor (M6PR) pathway. AMFA engineering of mAbs results in the generation of a bifunctional antibody that is designed to bind both the antigen and the M6PR. The improvement of the therapeutic potential by AMFA engineering was investigated using two antibodies directed against soluble antigens: infliximab (IFX), directed against tumor necrosis factor a (TNF-a), and bevacizumab (BVZ), directed against the vascular endothelial growth factor (VEGF). AMFA conjugations to the antibodies were performed either on the oligosaccharidic chains of the antibodies or on the lysine residues. Both conjugations were controlled and reproducible and provided a novel affinity for the M6PR without altering the affinity for the antigen. The grafting of AMFA to mAb increased their cellular uptake through an M6PR-dependent mechanism. The antigens were also 2.6 to 5.7 times more internalized by mAb-AMFA and rapidly degraded in the cells. Additional cell culture studies also proved the significantly higher efficacy of IFX-AMFA and BVZ-AMFA compared to their unconjugated counterparts in inhibiting TNF-a and VEGF activities. Finally, studies in a zebrafish embryo model of angiogenesis and in xenografted chick embryos showed that BVZ-AMFA was more effective than BVZ in reducing angiogenesis. These results demonstrate that AMFA grafting induces the degradation of soluble antigens and a significant increase in the therapeutic efficacy. Engineering with mannose 6phosphate analogues has the potential to develop a new class of antibodies for autoimmune and inflammatory diseases.